Targeting the B-Cell Pathway in Lupus Nephritis: Current Evidence and Future Perspectives. (26th September 2013) - Pateinakis, Panagiotis; Pyrpasopoulou, Athina
Abstract : Nephritis represents a frequent, severe complication of systemic lupus erythematosus. Autoantibodies appear to be fundamental in the pathogenesis of lupus nephritis. Several hypotheses are currently experimentally tested to further elucidate the direct induction of inflammation through interaction of the pathological autoantibodies with intrinsic glomerular components and the triggering of a complement-driven autoinflammatory cascade. B-cells have, in the last decade, emerged as a promising new therapeutic target, as biological treatments successfully attempting B-cell depletion, inhibition of B-cell proliferation and differentiation, or modulation of B-cell function have become bioengineered. Clinical trials have so far proved controversial regarding the efficacy of these new agents. Thus, despite the short and long-term side effects associated with immunosuppressive treatment alternative emerging treatments are still regarded "rescue" regimens in refractory patients. In an effort to accurately evaluate the potential of these therapies in lupus nephritis, several issues have been raised mainly in terms of patient selection criteria and trial duration. This review aims to expand on the proposed pathophysiologic mechanisms implicating the B-cell pathway in the pathogenesis of lupus nephritis and summarize current knowledge obtained from clinical trials introducing these biologics in its treatment. Finally, it will elaborate on potential applications of currently available biologic agents and forthcoming treatment options.